2001
DOI: 10.1590/s0102-37722001000200010
|View full text |Cite
|
Sign up to set email alerts
|

Understanding families in India: a reflection of societal changes

Abstract: -Literature on family studies in India has grown to a large extent in the last two decades, although such studies are scattered. This article presents socio-demographic data on families in India aiming to provide bases for analyzing research, particularly in the area of family development. Indian families are classified as patrilineal and matrilineal according to the lineage or descent by father or mother. The family structure is conceptualized as the configuration of role, power, and status and relationships … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 13 publications
0
50
0
2
Order By: Relevance
“…The family structure in countries like India is to a considerable extent, influenced by patriarchal customs. Such setup encourages families to leave all the decision-making power to males (Sonawat, 2001). …”
Section: Sociological Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…The family structure in countries like India is to a considerable extent, influenced by patriarchal customs. Such setup encourages families to leave all the decision-making power to males (Sonawat, 2001). …”
Section: Sociological Approachmentioning
confidence: 99%
“…Families in Asian cultures are achieving quite positive changes regarding patriarchal structures and the perception of women (Sonawat, 2001), and the historical role of women is seen as one that must be respected. However, females are still having trouble improving the way they are perceived, as well as being able to effectively practice their rights due to gender discrimination.…”
Section: Sociological Approachmentioning
confidence: 99%
“…A family occurs out of marriage (Nambi, 2005) and couples stay together without marriage, but single-parent families and childless families are not well accepted as complete or standard families in India (Tata Institute of Social Sciences, as cited in Sonawat, 2001). Srivastava (2013) reported that in India, it is almost compulsory for every individual to get married and settle down; not getting married is considered a stigma, especially in the case of women.…”
Section: Abstract Divorce Marital Distress Newlywed Couplementioning
confidence: 99%
“…The Indian population can be divided on the basis of its religious composition. In 1981, the overwhelming majority (82.35%) was Hindus, followed by 11.74% Muslims, 2.44% Christians, 1.97% Sikhs, and 1.57% others (Sonawat, 2001). All the religions have their own traditions and customs that regulate the institution of marriage (Kallampally et al, 2008;Nambi, 2005).…”
Section: Indian Religious and Legal Views On Marriagementioning
confidence: 99%
See 1 more Smart Citation